Developing the inner teacher: guiding the reflective practice of first year preservice teachers. Issue 1 (2nd January 2016) - Penn-Edwards, Sorrel; Donnison, Sharn; Albion, Lisa
Abstract: First year Australian Initial Teacher Education students are at a high risk of not completing their studies, particularly in the transition into their tertiary studies in first year, and then if achieving graduation, many are likely to leave the profession in the early years. While the reasons vary, it is known that early departure from a career in teaching can signal a lack of personal resilience and emotional coping skills. As teacher educators, we aimed to ameliorate this through using an intensively reflective first year course curriculum to assist preservice teachers in developing these essential qualities and skills. Our curriculum adopts a framework of self managed learning and personal growth through immersive reflective practice leading to the development of a personalised pedagogy of self . In line with these tenets, our curriculum story unfolds through the reflections of first year preservice teachers and academic staff teaching into this first year course.